1995
DOI: 10.1111/j.1365-2265.1995.tb02928.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular function and glucocorticoid replacement in patients with hypopituitarism

Abstract: In contrast to other studies we have failed to confirm cardiovascular dysfunction in GH deficient hypopituitary adults. Indeed, cardiovascular protection may be conferred on this group by the lower BP levels. Although a reduction in hydrocortisone dose was well tolerated in all patients, it appeared to confer no additional clinical benefit over the 3-month study period. In view of the conflicting data on cardiovascular function in hypopituitary patients, further prospective mortality studies are required in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 31 publications
4
55
0
Order By: Relevance
“…Al-Shoumer et al (60) reported that hypopituitary patients on GC replacement were more insulin resistant in the mornings when HC was administered than in the mornings when no HC was given. In contrast, Dunne et al (61) found no significant difference in blood pressure and glucose metabolism over a 3-month period when reducing the daily dose of HC from 30 to 15 mg. This is in accordance with a report from McConnell et al (62) who found glucose metabolism to be similar in 15 ACTH-insufficient patients who, in a randomized cross-over study, received either i.v.…”
Section: Adrenocorticoid Axismentioning
confidence: 94%
“…Al-Shoumer et al (60) reported that hypopituitary patients on GC replacement were more insulin resistant in the mornings when HC was administered than in the mornings when no HC was given. In contrast, Dunne et al (61) found no significant difference in blood pressure and glucose metabolism over a 3-month period when reducing the daily dose of HC from 30 to 15 mg. This is in accordance with a report from McConnell et al (62) who found glucose metabolism to be similar in 15 ACTH-insufficient patients who, in a randomized cross-over study, received either i.v.…”
Section: Adrenocorticoid Axismentioning
confidence: 94%
“…This has been attributed to loss of b 2 -adrenoceptor-permissive effect of glucocorticoids in the heart due to b 2 -adrenoceptor density reduction, as shown in lymphocytes (13). A myocardial systolic dysfunction, assessed by echocardiography, has been described in patients with panhypopituitarism (14), but it has not been confirmed in other studies (15).…”
Section: Discussionmentioning
confidence: 85%
“…Patients with hypopituitarism have an increased prevalence of conventional cardiovascular risk factors, including obesity with central fat distribution, insulin resistance and dyslipoproteinemia [4]. Endothelial dysfunction and increased intimal-medial thickness (IMT) have also been described in these patients [5]. Until now, despite discrepancies among studies, growth hormone deficiency is the most well-known risk factor [4,6,7] of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%